Revisión Documental sobre el Conflicto Armado y la Muerte de Líderes Sociales en Colombia entre los Años 2014 y 2021: Un Análisis desde la Psicología Social (2022)
This is an investigative proposal regarding the Colombian armed conflict, murder and/or deaths of social leaders, with the objective of analyzing the current state of the investigation regarding the internal armed conflict in Colombia and the murder of social leaders from a Social Psychology perspective. , from a documentary review approach, this will be complemented with aspects around this problem, the possible approaches of visualization, shortcomings or investigative gaps of this topic